Characterizing The Effect of Thermal Annealing Process on the Physical and Structural Properties of Polybutester Suture Fibers.: Life Sciences - Material Science - M. Ali , Afaf; H Amin , Ali; M. Z, Fatma (International Journal of Life Science and Pharma Research, 2022)
In this work the effect of thermal annealing treatment on the different physical, optical and structural of surgical suture fibers were considered. Polybutester monofilaments suture fibers were thermally annealed at temperatures fluctuating from 50-130? for two different periods of 60 and 120 min. The thermal-treatment was supported using taut end settings. Multiple-beam Fizeau fringes in transmission and X-ray diffraction techniques were used to measure the physical and structural properties of the tested sutures. Such as refractive indices, birefringence, dielectric constant, polarizability, dielectric susceptibility and the crystallinity. From the obtained measured data , there was a noticeable increase in the physical properties and crystallinity throughout the annealing process for annealing time 120 min. which indicates that a new reorientation of Novafil suture molecules was performed, which will improve the mechanical properties of the sutures. This is a significant enhancement for these suture fibers to broaden their medical use and improve their clinical results. The new molecular reorientation of the Novafil surgical sutures was performed using the annealing process which demonstrates the polymer-chain relaxation during the thermal annealing process. Micro Interferograms were used to illustrate these findings.